Study of Four Element Microstrip Antenna Array Using Patch Type Electromagnetic Band Gap Structure - Rao, K. P.; Hunagund, P. V.; Vani, R. M. (Engineering, Technology & Applied Science Research, 2018)
This paper describes enhancements in the performance of four element microstrip antenna array. The conventional microstrip antenna array is producing gain equal to 6.81dB. With the introduction of U shape patch type electromagnetic band gap structure, the proposed microstrip antenna array is producing an improved gain of 20.33dB. It is producing reduced mutual coupling of -31.44, -36.41 and -31.62dB respectively. The radiation characteristics of the proposed microstrip antenna array are improved with appreciable decrease in back lobe radiation and increase in forward power. It is resonating at single band at 5.53GHz, producing an overall bandwidth of 109.45%, against 4.89% of conventional microstrip antenna array. Microstrip antenna arrays are designed using Mentor Graphics IE3D software and measured results are obtained using vector network analyzer.